2013
DOI: 10.1111/vop.12061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retrobulbar nerve block on heart rate variability during enucleation in horses under general anesthesia

Abstract: Heart rate variability is a sensitive, non-invasive parameter to obtain sympathovagal stimulations during general anesthesia. The retrobulbar block can prevent heart rate decrease associated with initiation of the oculocardiac reflex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Frequency‐derived measures of HRV in the present study were not significantly different when the groups were stratified by lesion type. These results were similar to those previously reported for the perioperative period in a small group of horses that underwent general anesthesia and retrobulbar analgesia for enucleation . However, the LF/HF 5 min, LF/HF 30 min , LF power 5 min , LF power 30 min , and HF power 5 min were significantly different between survivors and nonsurvivors, suggesting sympathovagal imbalance, increased sympathetic tone, and reduced vagal modulation of heart rate in nonsurvivors, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Frequency‐derived measures of HRV in the present study were not significantly different when the groups were stratified by lesion type. These results were similar to those previously reported for the perioperative period in a small group of horses that underwent general anesthesia and retrobulbar analgesia for enucleation . However, the LF/HF 5 min, LF/HF 30 min , LF power 5 min , LF power 30 min , and HF power 5 min were significantly different between survivors and nonsurvivors, suggesting sympathovagal imbalance, increased sympathetic tone, and reduced vagal modulation of heart rate in nonsurvivors, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…[11][12][13] Finally, these techniques reduce the incidence of the oculocardiac reflex, which can result in severe bradyarrhythmias and, rarely, asystole. [3][4][5][6][14][15][16][17] In humans, RBA has been considered the criterionreferenced standard for provision of regional anesthesia during many ophthalmic procedures. It is achieved by injecting 2 to 5 mL of an anesthetic agent intraconally (inside the muscle cone created by the extraocular muscles).…”
mentioning
confidence: 99%
“…There were no significant changes observed in PR, RR and SpO2 in rabbits, remaining within the physiological ranges for this species (HEDENQVIST, 2008). The retrobulbar block can prevent heart rate alterations, mainly when related to a decrease associated with initiation of the oculocardiac reflex (OEL et al, 2014). Errando et al (1999) reported an increase of SAP, DAP and MAP due to sympathetic stimulation, after parenteral ketamine administration.…”
Section: Discussionmentioning
confidence: 99%